Optimization of Human Resources in Creating a Productive Entrepreneurial Environment in Schools - Ashari, Ratu Ayu; Wahira, Wahira (Journal of Education Method and Learning Strategy, 2025)
The development of modern education requires schools not only to focus on academic achievement but also on character formation, creativity, and entrepreneurial skills of students. In this context, the optimization of human resources (HR) becomes a strategic aspect in creating a productive entrepreneurial environment in schools. This study aims to analyze the role of HR in supporting entrepreneurship, identify factors influencing optimization, and formulate appropriate development strategies. The research method employs a literature review by examining previous studies and relevant literature on the contribution of principals, teachers, administrative staff, and educational policies in strengthening school-based entrepreneurship. The findings indicate that HR plays a vital role through visionary leadership, practice-based learning, efficient administrative management, and both internal and external collaboration. The optimization process is influenced by competence, continuous training, leadership support, facilities, motivation, and government policies such as the Merdeka Curriculum. Recommended strategies include capacity building through training, integrating entrepreneurial values across subjects, forming school entrepreneurship teams, developing partnerships with businesses, and utilizing digital technology for learning and marketing. This study concludes that well-managed and sustainable HR development can foster an innovative and productive school entrepreneurship ecosystem. The implication is that schools need to build a systematic entrepreneurial culture so that students are equipped not only with academic knowledge but also with entrepreneurial mindsets that are independent, creative, and competitive in facing global challenges.